PENGEMBANGAN MEDIA PEMBELAJARAN DIORAMA PADA MATERI UPAYA PELESTARIAN LINGKUNGAN UNTUK PESERTA DIDIK DI SDN PAGINTUNGAN - Siti Mayuni; Nana Hendracipta; Syachruroji Ahmad (Universitas Muhammadiyah Jakarta, 2023)
This research aims to find out how to develop diorama learning media on environmental preservation material for class V students at SDN Pagintungan, to find out the feasibility of the diorama learning media that researchers have developed, and to find out students' responses to diorama learning media. This research was conducted at Pagintung Elementary School with 20 class V students as research subjects. This type of research refers to the Borg & Gall development model which was then modified by Sugiyono which consists of 7 stages, namely problem analysis, data collection, product design, design validation, design revision, product testing and final results. The instruments used are questionnaires for product validation by a team of experts (media, materials and educators) and student response questionnaire sheets. Based on data analysis, it can be concluded that the diorama learning media for training understanding of material on environmental conservation efforts for class V students at SDN Pagintungan that has been developed is in the Very Appropriate category with a percentage of 91.3% from media experts, the Very Appropriate category with a percentage of 99.3% from material experts and the Very Eligible category with a percentage of 95% from expert educators. The students' response to diorama learning media in the trial with 20 respondents was 93% included in the Very Good category